Synthesis, structure and superconducting properties of the (Hg1-xRex)Sr-2(Nd1-yCay)Cu2O6+delta system - Hyatt, N; Gameson, I; Edwards, P (2004)
The synthesis, structure and superconducting properties of the (Hg1-xRex)Sr2(Nd1-yCay)Cu 2O6+δ system (with 0 ≤ x ≤ 0.2 and 0.2 ≤ y ≤ 0.6) have been investigated. Near single phase compositions with x = 0.2 and 0.2 ≤ y ≤ 0.6 may be prepared by solid state reaction at room pressure. The maximum Tc = 100 K in this system is found for the nominal composition (Hg0.8Re0.2)Sr2(Nd0.6 Ca0.4)Cu2O6+δ. Rietveld analysis of time-of-flight neutron powder diffraction data from a sample with the refined composition Hg0.78Re0.22Sr2Nd0.59 Ca0.41Cu2O6.88 indicates that the rhenium cation in the (Hg,Re)Oδ layer of this material is hexavalent and six coordinate. On the basis of x-ray and neutron powder diffraction data, the Hg and Re cations in the (Hg,Re)Oδ layer of Hg0.78Re0.22Sr2Nd0.59 Ca0.41Cu2O6.88 appear to be randomly distributed, in contrast to the ordered nature of these cations in similar materials prepared by high pressure methods. The irreversibility field of essentially optimally doped Hg0.78Re0.22Sr2 Nd0.59Ca0.41Cu2O6.88 indicates no enhancement of the kind reported in similar materials prepared under high pressure. We suggest that this difference may be associated with (dis)ordering of the Hg and Re cations in the (Hg,Re)Oδ layer of these materials.